Digital Trend as the Effort for the Effectiveness of Legal Assistance at the Village Manager Level: Challenges and Opportunities. A Systematic Literature Review - Sardjana Orba Manullang (Cross-Border Journal of Business Management, 2021)
The digital trend is now not only among academics and top-level government policymaking officials. However, to streamline and innovate the performance of the village level apparatus, it also needs to be considered. To prove the effectiveness of this trend, between an opportunity and a challenge, we try to collect as much evidence as possible from previous studies that we are looking for electronically, such as published journals, government regulations at home and abroad, and national newspapers. We have systematically reviewed all of these documents and ensured that the study would answer the problem of this study validly and reliably regarding the results. We analyze under a phenomenological approach, including coding systems, evaluation, interpretation, and conclusion. So, based on the available data, we conclude that the trend of computerization among village officials to improve the quality of work is time to be applied and foster their human resources.